Polarimetric SAR imaging : theory and applications - Yamaguchi, Yoshio, 1954- (Boca Raton : CRC Press, 2020)
"Radar polarimetry has been used for the precise monitoring of Earth's surface. This book explains the basic polarimetry concept and its diverse applications such as deforestation, tree classification, landslide detection, tsunamis, volcano eruptions and ash distribution, snow accumulation, rice field monitoring, urban area exploration, ship detection, etc., using actual data sets taken by Advanced Land Observing Satellite (ALOS and ALOS2). Fully color-coded images generated by polarimetric techniques makes it easy to understand, and will help students and radar experts to use radar polarimetry in their academic and application fields"--
Wave polarimetry -- Scattering polarimetry -- Polarization matrices -- H/A/[alpha symbol] polarimetric decomposition -- Compound scattering matrix -- Scattering mechanisms and modeling -- Scattering power decomposition -- Correlation and similarity -- Polarimetric synthetic aperture radar -- Material constant -- Interpretation of polSAR images -- Surface scattering -- Double bounce scattering -- Volume scattering.
"This book is a revised version of the Japanese edition in 2007 plus addition of several recent observation results after 2007."
OCLC-licensed vendor bibliographic record.
Keywords: Polarimetric remote sensing; Polarimetry; Remote-sensing images; Synthetic aperture radar; S-matrix theory; TECHNOLOGY / Remote Sensing; TECHNOLOGY / Imaging Systems; SCIENCE / Earth Sciences / General